2015
DOI: 10.1021/acs.est.5b01408
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Concentrations of U and Co-occurring Metals in Abandoned Mine Wastes in a Northeastern Arizona Native American Community

Abstract: The chemical interactions of U and co-occurring metals in abandoned mine wastes in a Native American community in northeastern Arizona were investigated using spectroscopy, microscopy and aqueous chemistry. The concentrations of U (67-169 μg L(-1)) in spring water samples exceed the EPA maximum contaminant limit of 30 μg L(-1). Elevated U (6,614 mg kg(-1)), V (15,814 mg kg(-1)), and As (40 mg kg(-1)) concentrations were detected in mine waste solids. Spectroscopy (XPS and XANES) solid analyses identified U (VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 45 publications
9
117
1
Order By: Relevance
“…Sediment samples from the site included mine waste and baseline reference soil (background soil) previously characterized by Blake et al, 2015. 6 The Blake et al study used powder X-ray diffraction to identify quartz (SiO 2 ; 59%) potassium feldspar (KAlSi 3 O 8 ; 34%), and kaolinite (Al 2 Si 2 O 5 (OH) 4 ; 7%) as the major mineralogical constituents. Additionally the co-occurrence of U and V, and predominance of U(VI) and V(V) were identified using microscopy, X-ray photoelectron spectroscopy (XPS), and X-ray absorption near edge spectroscopy (XANES) techniques.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sediment samples from the site included mine waste and baseline reference soil (background soil) previously characterized by Blake et al, 2015. 6 The Blake et al study used powder X-ray diffraction to identify quartz (SiO 2 ; 59%) potassium feldspar (KAlSi 3 O 8 ; 34%), and kaolinite (Al 2 Si 2 O 5 (OH) 4 ; 7%) as the major mineralogical constituents. Additionally the co-occurrence of U and V, and predominance of U(VI) and V(V) were identified using microscopy, X-ray photoelectron spectroscopy (XPS), and X-ray absorption near edge spectroscopy (XANES) techniques.…”
Section: Methodsmentioning
confidence: 99%
“…6 Results showed that U and V co-occur in mine wastes predominantly as U(VI) and V(V). The Extended X-ray absorption fine structure (EXAFS) fittings suggest that U and V coordination in these mine waste samples is similar to that of minerals such as carnotite or tyuyamunite.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations